2020
DOI: 10.1111/myc.13085
|View full text |Cite
|
Sign up to set email alerts
|

Persistent vs non‐persistent candidaemia in adult patients in 2007‐2016: A retrospective cohort study

Abstract: Mycoses. 2020;63:617-624. | 617 wileyonlinelibrary.com/journal/myc | INTRODUC TI ONCandida is a major cause of nosocomial infections, 1 and candidaemia causes significant mortality ranging between 30% and 45%. [2][3][4][5] Furthermore, candidaemia generates significant healthcare costs. 2 Its main complications include metastatic infection foci and death. 6 Persistent candidaemia (PC) is frequently recognised as another complication of candidaemia. Underlying factors that can influence the persistence of blood… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

10
14
6

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(30 citation statements)
references
References 41 publications
10
14
6
Order By: Relevance
“…Currently, it has been shown that ineffective empirical treatment was associated with persistent candidemia in adult patients. 31 There are reports showing an increase in infections caused by non-albicans species, [26][27][28] while in our series both Candida albicans and non-albicans species were found equally often only in deep-site cultures. Furthermore, in blood cultures and central line specimens, Candida albicans was still more prevalent.…”
Section: Discussionsupporting
confidence: 43%
See 1 more Smart Citation
“…Currently, it has been shown that ineffective empirical treatment was associated with persistent candidemia in adult patients. 31 There are reports showing an increase in infections caused by non-albicans species, [26][27][28] while in our series both Candida albicans and non-albicans species were found equally often only in deep-site cultures. Furthermore, in blood cultures and central line specimens, Candida albicans was still more prevalent.…”
Section: Discussionsupporting
confidence: 43%
“…However, four of six (67%) of non‐albicans species were resistant to fluconazole. Currently, it has been shown that ineffective empirical treatment was associated with persistent candidemia in adult patients 31 . There are reports showing an increase in infections caused by non ‐ albicans species, 26‐28 while in our series both Candida albicans and non‐albicans species were found equally often only in deep‐site cultures.…”
Section: Discussionsupporting
confidence: 39%
“…However, even with catheter removal, mortality rates remain high in the setting of invasive candidiasis (Andes et al, 2012). The observation that removal of catheters decreases the risk of persistent candidemia and rate of mortality suggests that biofilm formation plays a major role in the pathogenesis of invasive candidiasis (Andes et al, 2012;Ala-Houhala and Anttila, 2020).…”
Section: Introductionmentioning
confidence: 99%
“…Although there have been multicenter studies that did not reach a conclusion on the importance of early CVC removal to the outcomes [ 31 , 32 , 33 ], we did find that delayed CVC removal in neonates with candidemia was independently associated with final in-hospital mortality. This can probably be explained by these patients being more likely to have persistent candidemia and/or breakthrough candidemia, which is associated with final adverse outcomes [ 34 , 35 ]. However, in cases when the catheter is not the source of sepsis, it deserves a prospective, randomized controlled trial to document whether prompt catheter removal contributes significantly to the outcomes as it is often difficult to reinsert the CVC during the critically ill period.…”
Section: Discussionmentioning
confidence: 99%